Preferential associated anomalies in 818 cases of microtia in South america - Luquetti, Daniela V. (2013)
The etiology of microtia remains unknown in most cases. The identification of patterns of associated anomalies (i.e., other anomalies that occur with a given congenital anomaly in a higher than expected frequency), is a methodology that has been used for research into the etiology of birth defects. We conducted a study based on cases of microtia that were diagnosed from more than 5 million live (LB)- and stillbirths (SB) examined in hospitals participating in ECLAMC (Latin American Collaborative Study of Congenital Malformations) between 1967 and 2009. We identified 818 LB and SB with microtia and at least one additional non-related major congenital anomaly (cases) and 15,969 LB and SB with two or more unrelated major congenital anomalies except microtia (controls). A logistic regression analysis was performed to identify the congenital anomalies preferentially associated with microtia. Preferential associations were observed for 10 congenital anomalies, most of them in the craniofacial region, including facial asymmetry, choanal atresia, and eyelid colobomata. The analysis by type of microtia showed that for anomalies such as cleft lip and palate, macrostomia, and limb reduction defects, the frequency increased with the severity of the microtia. In contrast, for other anomalies the frequency tended to be the same across all types of microtia. Based on these results we will integrate data on the developmental pathways related to preferentially associated congenital anomalies for future studies investigating the etiology of microtia.